2017
DOI: 10.1093/gbe/evx226
|View full text |Cite
|
Sign up to set email alerts
|

RAD-Seq Reveals Patterns of Additive Polygenic Variation Caused by Spatially-Varying Selection in the American Eel (Anguilla rostrata)

Abstract: The American Eel (Anguilla rostrata) has an exceptional life cycle characterized by panmictic reproduction at the species scale, random dispersal, and selection in a highly heterogeneous habitat extending from subtropical to subarctic latitudes. The genetic consequences of spatially-varying selection in this species have been investigated for decades, revealing subtle clines in allele frequency at a few loci that contrast with complete panmixia on the vast majority of the genome. Because reproduction homogeniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 68 publications
(97 reference statements)
5
49
0
Order By: Relevance
“…Specifically, our genotype‐environmental association analyses suggest genotype associations with habitat features such as local reef geology, reef complexity, and exposure to wave power and ocean currents that vary over scales of tens to hundreds of metres (Ierodiaconou et al, ; Young et al, ). Evidence of finescale adaptive genetic structuring is unusual in dispersive marine species, with a few exceptions (Babin, Gagnaire, Pavey, & Bernatchez, ; Sherman & Ayre, ). While we cannot completely rule out the influence of false positives, each genotype‐environment association (GEA) detected was corrected for spatial structure and distance, and our sampling regime contrasted genetic variation across distinct habitat types present both within and between western, central, and eastern regions of the state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, our genotype‐environmental association analyses suggest genotype associations with habitat features such as local reef geology, reef complexity, and exposure to wave power and ocean currents that vary over scales of tens to hundreds of metres (Ierodiaconou et al, ; Young et al, ). Evidence of finescale adaptive genetic structuring is unusual in dispersive marine species, with a few exceptions (Babin, Gagnaire, Pavey, & Bernatchez, ; Sherman & Ayre, ). While we cannot completely rule out the influence of false positives, each genotype‐environment association (GEA) detected was corrected for spatial structure and distance, and our sampling regime contrasted genetic variation across distinct habitat types present both within and between western, central, and eastern regions of the state.…”
Section: Discussionmentioning
confidence: 99%
“…This is not a novel finding; evidence of phenotype‐environment mismatches impacting recruitment dynamics and reducing population connectivity in dispersive marine species is well documented and summarised in Marshall et al (). Natural selection could potentially occur at pre‐ or post‐settlement stages in H. rubra, as seen in other marine and diadromous taxa (Babin et al, ; Sherman & Ayre, ). In some marine species, environmental cues influence the settlement of larvae from the water column (Harrington, Fabricius, De'ath, & Negri, ; Rodriguez, Ojeda, & Inestrosa, ; Sneed, Sharp, Ritchie, & Paul, ), with encrusting coralline algae, macroalgae, and mucus trails reported to be potential settlement cues for Haliotids (Huggett, de Nys, Williamson, Heasman, & Steinberg, ; Morse, Froyd, & Morse, ; Takami, Kawamura, & Yamashita, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a final step for the multilocus approach, we calculated a polygenic score to assess the individual cumulative adaptive genetic variation associated with each environmental variable tested (Babin, Gagnaire, Pavey, & Bernatchez, 2017;Gagnaire & Gaggiotti, 2016).…”
Section: Peresmentioning
confidence: 99%
“…Evidence of local adaptation associated with environmental conditions in marine populations is growing, challenging the dogma that a high degree of gene flow precludes adaptive divergence in the ocean (Bernatchez, ; Sanford & Kelly, ). Empirical studies have identified key environmental predictors of adaptive genetic variation across environmental gradients in marine taxa including corals (Lundgren, Vera, Peplow, Manel, & van Oppen, ), eels (Babin, Gagnaire, Pavey, & Bernatchez, ; Gagnaire et al, ), sticklebacks (Guo, DeFaveri, Sotelo, Nair, & Merilä, ), lobsters (Benestan et al, ), and Pacific (Hecht, Matala, Hess, & Narum, ) and Atlantic (Jeffery et al, ) salmon.…”
Section: Introductionmentioning
confidence: 99%